Variations in maternal care associated with differences in female rat reproductive behavior in a group‐mating environment. Issue 8 (27th August 2012) - Prior, Karen M.; Meaney, Michael J.; Cameron, Nicole M.
Abstract Maternal care influences the development of sexual behavior in pair mating rats, under laboratory conditions. This study examined the effect of variations in maternal care in a group‐mating condition. Groups of two low and two high licking/grooming (LG) female offspring mated with two males in a large pacing chamber for 36 hr. Sexual behaviors were scored for the first 15 vaginal–cervical stimulations (VCS) and the entire 36 hr. Low LG females spent more time mating, required more time to receive an intromission after entering the male compartment. They also received more ejaculations compared to high LG females during the first 15 VCS. This difference disappeared as mating continued. Males were more responsive to high than low females. No pregnancy rate difference was seen between the two female phenotypes, demonstrating that variation in maternal care received results in two mating strategies that are both reproductively successful under group‐mating conditions. © 2012 Wiley Periodicals, Inc. Dev Psychobiol 55: 838–848, 2013.